The role of trust, power and risk-taking in determining potential tax compliance: experimental evidence from a university setting - Saied, Mai (AUC Knowledge Fountain, 2019)
The core aim of this thesis is to test the main assumptions of the slippery slope framework through assessing the degree of perceived trust and power in and towards the government authorities. The slippery slope framework assimilates various behavioral and non-behavioral factors that affect the two main determinates of the tax compliance behavior: trust and power. This research builds on a current working paper that conducted a cross-cultural study on 44 countries to test the tax compliance of youth among different countries; among the top ten authors of this international project was Professor Medhat Hassenin. The contribution of this thesis is to extend the prior study by administering the analysis on a different sample and an additional variable: risk taking. This thesis, besides testing the slippery slope framework, investigates the impact of risk taking on the tax compliance behavior. The data of this research was collected on a diversified sample of students at the American university in Cairo. The participants of this research were presented with different scenarios of trust and power, and their degree of risk taking was tested through a domain specific risk taking attitude scale. As predicted, the result of this study supports the main assumptions of the slippery slope framework and confirms the role of risk taking on the compliance behavior.